2003
DOI: 10.1074/jbc.m304079200
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Hypoxia-inducible Factor-2 in PC12 Cells by Nerve Growth Factor Stimulation

Abstract: Cellular responses to low oxygen tension are mediated, at least in part, by the activation of the hypoxiainducible factors (HIFs). In the presence of oxygen, specific HIF residues become hydroxylated by the action of a recently described group of dioxygenases. These posttranslational modifications target HIF for proteosomal degradation and prevent its transcriptional activity. Despite these detailed studies, little is known about the regulation of HIF by stimuli other than hypoxia. Here we report that, in rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Up-regulation of Their Gene Expression-It has been reported that hypoxia up-regulates EGLN1 and -3, but not EGLN2, mRNA in several cell types including HeLa cells (22), U2OS osteosarcoma cells (26), rat pheochromocytoma PC12 cells (27), and human cardiovascular cells (28). In addition to these cell lines, we have found that EGLN1 is up-regulated in HEK293, HepG2, and Jurkat cells and EGLN3 in HepG2 and Jurkat cells (Fig.…”
Section: Hypoxia Increases Egln1 and Egln3 Mrna Levels Bymentioning
confidence: 68%
See 2 more Smart Citations
“…Up-regulation of Their Gene Expression-It has been reported that hypoxia up-regulates EGLN1 and -3, but not EGLN2, mRNA in several cell types including HeLa cells (22), U2OS osteosarcoma cells (26), rat pheochromocytoma PC12 cells (27), and human cardiovascular cells (28). In addition to these cell lines, we have found that EGLN1 is up-regulated in HEK293, HepG2, and Jurkat cells and EGLN3 in HepG2 and Jurkat cells (Fig.…”
Section: Hypoxia Increases Egln1 and Egln3 Mrna Levels Bymentioning
confidence: 68%
“…In most of the cases reported, the induction of EGLN3 mRNA is much more prominent than that of EGLN1. Moreover, the increased mRNA levels correlate with increased EGLN activity (27). As a whole, these results suggest that EGLN1 and -3 can be targets of the pVHL/HIF pathway, but no evidence for this hypothesis has been reported.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Several oxidation-sensitive transcription factors tested with a priori assumption, such as c-myc, hypoxia induced factor-2α (HIF-2α), and the peroxisome proliferator-activated receptor-γ (PPAR-γ)) (Haddad et al, 2000;De Nigris et al, 2001;Naranjo-Suarez et al, 2003) showed significant differential regulation, e.g., M4/G4: -17 (p = 0.002), 2.2 (p = 0.027), and -2.3 (p = 0.024) fold expression, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For each sample, duplicate determinations were carried out, and the gene copy number was normalized to the amount of ␤-actin. The primer pairs used in this study have been reported elsewhere (34).…”
Section: Methodsmentioning
confidence: 99%